POLITENESS STRATEGIES USED BY THE MAIN CHARACTER IN THE FILM ONWARD - Muhammad Lukmanul Hakim; Nine Febrie Novitasari (University of Muhammadiyah Malang, 2022)
It is essential to pay attention to the use of politeness strategies in communication, especially if the speaker and listener come from different cultures. People and cultures have been successfully visualized by Disney Pixar in their films that often expose their audiences to different cultural backgrounds of their characters. This research aimed at analyzing the politeness strategies used by the main character in a Disney Pixar animated adventure film Onward. The data in this descriptive qualitative research were analyzed by using the theories of politeness strategies proposed by Brown and Levinson (1987). The results indicate that Ian Lightfoot, the main character, uses a lot of bald-on-record strategies in communicating. This is closely related to the theme of the film in which there are many scenes showing emergencies that require quick action and orders for the safety of the main characters. In addition to that, the most-frequent-used politeness strategies done does not necessarily imply emotional closeness between speakers. The linguistic choices made by the main character were affected by the socio-cultural aspects formed in his society.